A novel single-gimbal control moment gyroscope driven by an ultrasonic motor. (April 2019) - Pan, Song; Xu, Zhangfan; Zhao, Chunsheng
This article presents a structure-compacted single-gimbal control moment gyroscope, which is directly driven by an ultrasonic motor. The momentum wheel and the ultrasonic motor are designed and optimized based on software simulation. Considering the gyroscope's dynamic disturbance and the nonlinearities of the ultrasonic motor, an expert control algorithm combining a two-degree-of-freedom pole placement controller with a pattern reasoning controller is designed for the gimbal servo system. The presented controller realizes a wide-range closed-loop speed control of the gimbal from 0.2 mrad/s to 1.6 rad/s, which is the base of the high stability and high precision of the control moment gyroscope. The presented control moment gyroscope and its controller board are manufactured and assembled for experiments. The experimental results show that the momentum wheel has almost no impact on the gimbal servo system at high speeds, but with the decrease in the gimbal speed the impact increases gradually.